2003
DOI: 10.1007/s00464-002-8763-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic inguinal hernia repair using an anatomically contoured three-dimensional mesh

Abstract: An anatomically contoured mesh for transabdominal preperitoneal hernia repair often requires no fixation, with minimal risk of neuropathy and less than a 0.5% patient-year recurrence rate. Recovery is excellent even with bilateral repair or some fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
2
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 11 publications
1
22
2
1
Order By: Relevance
“…27 Bell et al in their study found a recurrence rate of 0.42% after 23 months of follow up. 28 The results of this study are not truly comparable to previous studies as recurrence is a late phenomenon which can be best determined by further long term follow-up studies. 27,28 Lastly, 3D mesh was found to be slightly costly in this study as is evident by the fact that 3D mesh costs twice as that of the flat mesh.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…27 Bell et al in their study found a recurrence rate of 0.42% after 23 months of follow up. 28 The results of this study are not truly comparable to previous studies as recurrence is a late phenomenon which can be best determined by further long term follow-up studies. 27,28 Lastly, 3D mesh was found to be slightly costly in this study as is evident by the fact that 3D mesh costs twice as that of the flat mesh.…”
Section: Discussioncontrasting
confidence: 52%
“…28 The results of this study are not truly comparable to previous studies as recurrence is a late phenomenon which can be best determined by further long term follow-up studies. 27,28 Lastly, 3D mesh was found to be slightly costly in this study as is evident by the fact that 3D mesh costs twice as that of the flat mesh. However, elimination of tacks for fixation and shorter hospital stay may compensate for the increased cost of the 3D mesh.…”
Section: Discussioncontrasting
confidence: 52%
“…31 Patients in present study were explained the cost of both meshes and were given free choice regarding the use of mesh. No doubt, the unique shape of 3D mesh is designed to conform to the inguinal anatomy, contour minimizes buckling and design reduces the need for fixation, 18 still in comparison to polypropylene mesh, 3D mesh was found to be costly in present study, as is obvious by the fact that the cost of 3D mesh is twice than that of the flat mesh. We assume that, elimination of tacks and shorter hospital stay may reduce the overall cost of laparoscopic inguinal hernia repair using 3D mesh.…”
Section: Discussionmentioning
confidence: 73%
“…Recovery is excellent even with bilateral repair or some fixation. 18 The mesh fixation time in 3D mesh was 10.6±4.31 minutes and 14.4±2.74 minutes in PP mesh. The difference was statistically significant (p value-0.0002).…”
Section: Discussionmentioning
confidence: 88%
“…This has prompted surgeons to take a new look at fixation of the mesh. When fixation is reduced or completely avoided, chronic pain is eliminated without increasing recurrence rates [12,16]. These newer studies suggest that the laparoscopic hernia repair may have the unexpected potential of reducing the incidence chronic pain below levels previously reported after conventional anterior repairs.…”
Section: How Far Have We Come?mentioning
confidence: 99%